Pengembangan Interactive Virtual Tour PT. Schneider Electric Manufacturing Batam - Pungky Agustine; Paniophan Siregar (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
Schneider Electric Manufacturing Batam Virtual Tour is good enough using 360º interactive photos, but in order to create a new form of innovation that will give a better user experience this study will focus on how to develop the virtual tour using 360º videos and interactive objects. Video is considered to give a better engagement than photo in a term of effectiveness because video is a combination of visuals and sounds. This study was conducted using Villamil-Molina method as a method on how the product will be produced and developed. Villamil-Molina method consists of 5 main basic steps: development, pre-production, production, post-production and delivery. The virtual tour result will be analyzed for its usability rate using System Usability Scale (SUS) in order to know if the usability rate already meet the standard or still below average. The research resulted in several conclusions: (1) The product was successfully produced, a new virtual tour with the development of interactivity, additional locations, and additional informations. (2) Based on the System Usability Scale (SUS) score, the result shows virtual tour’s adjective rating is “Good” (B) with the final score of 72.15.